Azacitidine improves the T-cell repertoire in patients with myelodysplastic syndromes and acute myeloid leukemia with multilineage dysplasia. Issue 9 (September 2015) - Fozza, Claudio; Corda, Giovanna; Barraqueddu, Francesca; Virdis, Patrizia; Contini, Salvatore; Galleu, Antonio; Isoni, Antonella; Dore, Fausto; Angelucci, Emanuele; Longinotti, Maurizio
Highlights T-cell frequencies improve during Azacitidine therapy in MDS and AML with dysplasia. While on Azacitidine patients show a restoration of the CD4+ CDR3 diversity. The overall derangement of the T-cell repertoire gradually improves after Azacitidine.